Differential Harnack Estimates for a Semilinear Parabolic System - Hui Wu (Journal of Function Spaces)
In this paper, we prove differential Harnack inequalities for positive solutions of a semilinear parabolic system on hyperbolic space. We use the inequalities to construct classical Harnack estimates by integrating along space-time.